Now You Are Part of the Solution: Bioethicists' Contribution in Addressing Racialized Health Inequity - Kerr, Jelani (The Hastings Center report, 2022)
Neoliberalism (an economic approach emphasizing tax abatement, market deregulation, and social safety net reduction) promotes inequality and unfavorable health outcomes. These outcomes are exacerbated among racial and ethnic minorities, as this policy approach is often coupled with various forms of institutional racism. The combination of these factors translates into concerning population health disparities in the United States. More egalitarian policies could disproportionately affect the socially marginalized and help rectify these challenges. Given the social and cultural capital bioethicists have in the fields of medicine, public health, and policy, this group is uniquely positioned to help remediate racial and ethnic inequity. Moreover, the unique skill sets bioethicists employ (conflict resolution, mediation, negotiation, facilitating public engagement, policy analysis) can be useful to improving the health of the populous. Thus, bioethicists can play a key role in addressing the most concerning health challenges and inequities today.